2021
DOI: 10.30515/0131-6141-2021-82-2-85-89
|View full text |Cite
|
Sign up to set email alerts
|

Through war miles to the truths of Russian speech (to the 100th anniversary of the birth of V. P. Zhukov)

Abstract: The article briefly highlights the life path and scientific heritage of Vlas Platonovich Zhukov (1921– 1991), Doctor of Philology, Professor, Honoured Scientist of the RSFSR, one of the leading phraseologists in Russia. The constructive pillars of the scholar’s concept consisted in two oppositions: 1) a phraseological unit and a word 2) a word and a component of a phraseological unit. In line with this direction and using the method of phraseological application, a whole complex of fundamental problems can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This story is difficult and complicated. Throughout the entire period of our work, we have tried to preserve the continuity between scientists of different generations, talking about their achievements as we would talk about our parents who gave us life [32]. At the same time, we tried not to forget that, in those conditions when science and culture were under the almost complete control of I.V.…”
Section: Is the Second Brain Located In The Intestine?mentioning
confidence: 99%
See 1 more Smart Citation
“…This story is difficult and complicated. Throughout the entire period of our work, we have tried to preserve the continuity between scientists of different generations, talking about their achievements as we would talk about our parents who gave us life [32]. At the same time, we tried not to forget that, in those conditions when science and culture were under the almost complete control of I.V.…”
Section: Is the Second Brain Located In The Intestine?mentioning
confidence: 99%
“…Academician of the Academy of Sciences of the Soviet Union in the Department of Physiology (1984) Alexander Mikhailovich Ugolev (1926-1991) (Fig. 5), who first discovered parietal digestion [32] The brain can affect the intestinal microbiota. The normal microbiota is affected by stress-induced changes in the gastrointestinal tract: epithelial function, mucin production, entero-endocrine cell function, peristalsis, immune response Brain "Intestine brain" axis…”
Section: Is the Second Brain Located In The Intestine?mentioning
confidence: 99%
“…The earliest records of Lecanosticta in Asia originate from southern and eastern China (Fujian and Jiangsu provinces), Japan, and South Korea (Suto and Ougi 1998;Ye and Wu, 2011;Seo et al, 2012;Table S2) where diagnosis was confirmed using species-specific conventional PCR and sequencing, together with morphological methods. Zhukov et al (2013) identified the pathogen in Asian Russia (Sakhalin Island, less than 100 km north of the Japanese island of Hokkaido) on P. pumila (Pall.) Regel via morphological methods.…”
Section: Asiamentioning
confidence: 99%
“…Действительно, опубликовано немало книг о вкладе узбекистанцев в победу. Отметим работы следующих авторов: А.Ю.Безугольный, И.В.Быстрова, Т.Д.Джураев, Г.К.Жуков, З.Р.Ишанходжаева, Д.З.Муриев, В.С.Мурманцева, М.А.Рахимов, М.Я.Сухарь, Б.Шапошников, материалы международной научной конференции «Вторая мировая война в истории и памяти народов Центральной Азии: события, участники, символы» [1][2][3][4][5][6][7][8][9][10][11][12][13][14].…”
Section: Introductionunclassified